Beyond entrepreneurial cities - Peter North; Alexander Nurse (Métropoles)
This paper lays out the lineaments of a post-capitalist grassroots urbanism in response to climate change and resource depletion as an alternative to ‘business as usual’ economic development strategies focused on growth maximisation associated with the ‘entrepreneurial thesis’ of urban management. The paper argues that alternative development strategies that do what radical critics argue is necessary to avoid dangerous anthropogenic climate change lack legitimacy within political and economic elites. Debates about a city’s economic development policy are channelled into a technocratic process of identifying models of ‘green growth’ that reduces carbon emissions and generates new jobs and business opportunities in ways that some have labelled ‘post-political’. The paper argues that that radical grassroots critics are mounting a challenge to neoliberal conceptions of entrepreneurial urbanism and develops a manifesto for what a more strategic urban response to climate change might look like which draws on ‘diverse economies’ perspectives, and which opens up a contested political space for a progressive urban politics of resource crises and climate change. While these ideas are presently underdeveloped, their existence means that debates about sustainable development cannot be dismissed as uniformly post-political.